Farmacogenética do Gene TPMT na resposta A 6-Mercaptopurina, em pacientes com Leucemia Linfoblástica Aguda - LIMA, Carlos Henrique Vasconcelos de (Universidade Federal do Pará, 2017)
Acute Lymphoblastic Leukemia (ALL) is the most common type of cancer in children under 15 years of age. 6-mercaptopurine (6-MP) is one of the most widely used chemotherapeutic agents in the treatment of childhood ALL. Polymorphisms in thiopurine S-methyltransferase gene (TPMT) may be associated with individual variation in the response to treatment of childhood ALL, such as increased severe toxicity (grade 3 and 4). The aim of this study was to associate polymorphisms of TPMT gene: TPMT*2 (238G>C), TPMT*3A (460G>A and 719A>G), TPMT*3B (460G>A), TPMT*3C (719A>G), TPMT* 8 (644G>A) and intronic variant rs12201199 (94T>A) with the occurrence of serious toxicities in patients with ALL treated with 6-MP, in Northern Brazil. One hundred thirty-seven pediatric patients with ALL and treated at the Ophir Loyola Hospital in the state of Pará were investigated. The rs12201199 polymorphism was genotyped by real-time PCR (equipment 7500 Real-Time PCR System) and other polymorphisms were genotyped by direct sequencing using the automated sequencer ABI PRISM 3130 Genetic Analyzer (Applied Biosytems, CA, USA). The haplotypes among the studied polymorphisms were derived via maximum likelihood estimates using the program PHASE. A panel of 48 markers Ancestry Informative was used as genomic control in the sample and statistical analyses were performed using SPSS v.20.0 software (SPSS, Chicago, IL, USA). All statistical tests considered the probability (p) significant when ≤0, 05. In relation to the genomic ancestry, it was noted that the ethnic composition of ALL patients was 44% Caucasian, 22% African and 34% Amerindian. Among the reported toxicities, infectious was most prevalent (86%), followed by hematological (65%), gastrointestinal (64.8%) and central nervous system toxicity (29.9%). Allele frequency of polymorphism rs12201199 was 0.482 among the studied subjects. The most prevalent haplotype variants were TPMT*3A (7.6%), followed by TPMT*3C and TPMT*8, both 7.3%. There was no significant association between poor metabolism profiles of TPMT with none of the serious toxicities reported in the studied patients with LLA. However, our data show that there is a significant relationship between the polymorphism of TPMT gene (rs12201199) and the occurrence of severe infectious toxicity during treatment of childhood ALL. It has been observed that patients who have mutant homozygous AA genotype for this polymorphism in TPMT gene have 4.098 times higher risk of presenting severe infectious toxicity during the treatment for childhood ALL compared to those with the other genotypes. This result may be important to help predict risk of toxicity during treatment, contributing to a better individual prognosis of patients with childhood ALL.